PKM Pemanfaatan Teknologi Informasi Untuk Berbisnis Online Dalam Upaya Menumbuhkan Minat Berwirausaha Bagi Siswa SMA Katolik Ricci 2 Pondok Aren - Agus Umar Hamdani; Lis Suryadi; Gandung Triyono; Feby Lukito Wibowo (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Ricci Catholic High School 2 Pondok Aren is one of the private educational institutions that is oriented towards the process as a step of progress for students, accompanied by the development of life values ​​that have a balance between emotional, academic and spiritual intelligence. The Ricci 2 Catholic High School students consist of the principal and his staff, teachers, education staff and students. In the current industrial 4.0 era, Ricci 2 Pondok Aren Catholic High School has utilized the use of information and communication technology to support teaching and learning activities for students. Many extracurricular and non-extracurricular activities are held to increase students' knowledge and experience. One of the non-extracurricular activities is the business activity of selling school supplies through school cooperatives which are handled by student representatives who are members of the Student Organization (Osis). One of the superior products that are self-produced are uniforms and t-shirts with a market share that is only intended for school students and has not been able to reach markets outside of schools, this is due to limitations in available supporting facilities and infrastructure. In addition, although currently using Whatsapp media to do product marketing, the service is felt to be less than optimal. Based on the above conditions, we intend to provide an alternative solution by holding an introduction training to build an online business through a marketplace application in the hope that it can help build an entrepreneurial spirit, especially for students and generally for other school students. By having an entrepreneurial spirit, students of Ricci 2 Pondok Aren Catholic High School can develop existing businesses so that the economy of the school community can grow and develop well.